Early detection of hearing loss among IIUM Kuantan dental students - Habeeb Rahman, Tohirah; Lamri, Marina L. Alisaputri @ Marina (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2019)
Introduction: Dental practitioners are among the professionals that are at high risk of developing Noise Induced Hearing Loss (NIHL) over a long period of time as they are exposed to high level sound intensity from the dental equipment possibly on a daily basis. The anatomical structure of the ear causes the high frequency region of the cochlea to be commonly affected earlier by the continuous noise exposure. It is important to detect any changes to the cochlea that may lead to hearing loss as early as possible. Distortion Product Otoacoustic Emissions (DPOAEs) and High frequency Pure Tone Audiometry (HFPTA) were reported to be useful tools in early detection of NIHL (Gorga et. al., 1997; Mehrparvar et. al, 2011 & Somma et. al., 2008). The purpose of this study is to compare the hearing thresholds and otoacoustic emissions between dental students and non-dental students in IIUM Kuantan.